Kombinasi Stimulasi White Noise dan Pijat Bayi Terhadap Peningkatan Kualitas Tidur Bayi Usia 3-6 Bulan di PMB Bidan Aida - Afdhal Liranda; Bethania Soraya Siagian; Elprida Gulo; Fathiyah Aziz; Gita Anindita Tarihoran; Tiarnida Nababan (Universitas Pahlawan Tuanku Tambusai, 2026)
During infancy, ensuring optimal sleep quality plays a crucial role in supporting growth and development, particularly in promoting brain maturation. One approach to improving an infant’s sleep quality is through nonpharmacological interventions, such as infant massage and white noise therapy. Infant massage, through gentle tactile stimulation, is known to have a relaxing effect and increase the infant’s comfort. Meanwhile, white noise works by producing a constant sound that helps mask environmental noises that could potentially disrupt sleep. This study aims to analyze the effect of a combination of white noise stimulation and infant massage on improving sleep quality in infants aged 3–6 months at Aida Midwife’s Clinic. A quantitative approach using a single-group pre-experimental design (pre-test-post-test) was applied in this study. Infant sleep quality was evaluated before and after the intervention using a Guttman scale questionnaire. A Wilcoxon Signed-Rank test analysis of the 42 participants showed significant results with a p-value of 0.000 (p < 0.05), indicating that H₀ was rejected and H₁ was accepted. These findings suggest that the combination of white noise and infant massage significantly improves sleep quality in infants aged 3–6 months at Bidan Aida’s Maternal and Child Health Clinic.